2015
DOI: 10.1111/cei.12666
|View full text |Cite
|
Sign up to set email alerts
|

C1qrs292001 polymorphism and C1q antibodies in juvenile lupus and their relation to lupus nephritis

Abstract: SummaryC1q deficiency is related strongly to systemic lupus erythematosus (SLE), but very few and inconsistent studies explored the single nucleotide polymorphisms of the C1q gene in relation to juvenile SLE (jSLE) and lupus nephritis (LN). The objective of this study was to analyse whether C1q rs 292001 polymorphism is associated with SLE and disease phenotype, especially nephritis, and to investigate the relation between this polymorphism and clinical data, treatment outcome, serum level of C1q protein and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
(99 reference statements)
0
7
1
6
Order By: Relevance
“…Although a relation between high serum anti‐C1q levels and the presence of pLN, especially in its active state, has been proposed by several researchers, in the present study this relation was not confirmed . The serum anti‐C1q levels did not differ significantly between the pSLE patients with pLN and those without renal involvement.…”
Section: Discussioncontrasting
confidence: 95%
“…Although a relation between high serum anti‐C1q levels and the presence of pLN, especially in its active state, has been proposed by several researchers, in the present study this relation was not confirmed . The serum anti‐C1q levels did not differ significantly between the pSLE patients with pLN and those without renal involvement.…”
Section: Discussioncontrasting
confidence: 95%
“…C1q deficiency has been described as a high risk factor to develop SLE [139] but the genetically C1q deficiency in SLE is very rare [140] and the susceptibility risk of gene variants at the C1Q gene remains controversial [141,142]. Conversely, low levels of C1q are typically associated with disease flares and with the appearance of anti-C1q antibodies [80] which, in turn, are found in 20%–50% of SLE patients and in up to 100% of active proliferative LN patients [81].…”
Section: Autoantibody Specificities: An Antigenic Detonationmentioning
confidence: 99%
“…By evaluating 300 South Indian Tamil SLE patients, the authors identified a significantly higher frequency of heterozygous genotype of Q222R polymorphism in patients with nephritis than in those without (67% versus 53%, OR = 1.93) [ 39 ]. Some interesting data concerning the association between LN development and polymorphism on the gene codifying C1q have been recently published [ 41 , 42 ]. However, due to the small cohorts evaluated in these studies, their results should be confirmed in large populations.…”
Section: Renal Involvementmentioning
confidence: 99%